2013
DOI: 10.1111/jop.12058
|View full text |Cite
|
Sign up to set email alerts
|

A comparative immunohistochemical and immunophenotypical study on lymphocytes expression in patients affected by oral lichen planus

Abstract: We assume there is the responsibility of the expression of lymphocytes, not only type but also as quantity, in determining RL or WL manifestation of OLP. Circulating lymphocytes may have a role, too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Two main clinical forms of OLP have been detailed: White lesions (WL) are mostly asymptomatic, while atrophic and erosive lesions (RL) could result in intense discomfort (Carbone, Arduino, Carrozzo, Gandolfo, S et al., ). It was supposed that those different clinical types may be characterized by dissimilar cells and biological events (Janardhanam et al., ); moreover, the considerable reported accumulation of CD3, CD4, CD8, and CD56 lymphocytes in the lesion, together with the consequent cell‐mediated immunological mechanisms, could determine the evolving of OLP into RL manifestation, with a marked tissue damage; otherwise, WL are usually characterized by less tissue damage (Lorenzini, Viviano, Chisci, Chisci, & Picciotti, ), and this response could be induced by different immune‐mediated pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Two main clinical forms of OLP have been detailed: White lesions (WL) are mostly asymptomatic, while atrophic and erosive lesions (RL) could result in intense discomfort (Carbone, Arduino, Carrozzo, Gandolfo, S et al., ). It was supposed that those different clinical types may be characterized by dissimilar cells and biological events (Janardhanam et al., ); moreover, the considerable reported accumulation of CD3, CD4, CD8, and CD56 lymphocytes in the lesion, together with the consequent cell‐mediated immunological mechanisms, could determine the evolving of OLP into RL manifestation, with a marked tissue damage; otherwise, WL are usually characterized by less tissue damage (Lorenzini, Viviano, Chisci, Chisci, & Picciotti, ), and this response could be induced by different immune‐mediated pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Two main clinical forms have been described; white hyperkeratotic lesions (WL) are mostly asymptomatic, while atrophic and erosive lesions (RL) could result in intense discomfort (Carbone et al., ). It was supposed that these different clinical types may be characterized by dissimilar cells and biological events (Janardhanam et al., ); moreover, the considerable reported appeal of CD3, CD4, CD8 and CD56 lymphocytes in the lesion could determine the evolving of OLP into RL manifestation, with a marked tissue damage; WL could be evoked instead with a modulated way, characterized by lesser tissue damage (Lorenzini, Viviano, Chisci, Chisci, & Picciotti, ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that the increase in the ratio of CD8 + cells to FoxP3 + cells is associated with the development of several autoimmune diseases (Mempel et al, ), including the case of OLP‐I. It should be emphasised that in the cases of OLP, there is also a correlation between clinical characteristics and immune phenotype of T lymphocytes as erosive lesions, whose clinical characteristics were more exacerbated and therapeutic control was difficult, showed an increase in the amount of CD8 + lymphocytes and a decrease in the amount of FoxP3 + lymphocytes (Lei et al, ; Lorenzini, Viviano, Chisci, Chisci, & Picciotti, ). As for OLP‐HCV, some researchers believe that the chronic infection by HCV can produce an even more exacerbated expression of CD8 + T cells, which explains the development of complex clinical courses compared to lichenoid lesions and OLP‐I (Mega, Jiang, & Takagi, ).…”
Section: Discussionmentioning
confidence: 99%